Michael Moore is a big fat stupid white man - Hardy, David T.; Clarke, Jason (ReganBooks, 2004)
How, they ask, does Moore pull off his proletarian, "man-of-the-people" image so at odds with his lifestyle as a fabulously wealthy Manhattanite?
Keywords: Moore, Michael <1954 Apr. 23-> -- Miscellanea; Moore, Michael -- 1954-